Hubungan Gaya Kepemimpinan Transformasional Kepala Sekolah dengan Motivasi Kerja Guru di SMA Negeri Kecamatan Lubuk Basung - Ramahyani, Annisa; Marsidin, Sufyarma (ARZUSIN, 2023)
This research is motivated by transformational leadership, which refers to leaders who can motivate their followers to perform and manage their own interests for the benefit of the organization through individualized consideration, intellectual stimulation, and idealized influence, all of which result in extra effort from employees for better organizational effectiveness. However, in the Lubuk Basung District Public High School, it seems that transformational leadership has not been implemented effectively. The objectives of this research are to obtain data and information regarding 1) the transformational leadership of the school principal, 2) teacher's work motivation, and 3) the relationship between the school principal's transformational leadership style and teacher's work motivation in the Lubuk Basung District Public High School. The hypothesis proposed in this research is that there is a significant relationship between the school principal's transformational leadership and teacher's work motivation. This is a correlational research study. The population consists of all civil servant teachers teaching in the Lubuk Basung District Public High School, with a total of 83 individuals. The research sample is obtained using a proportional stratified random sampling technique with the Solvin formula, resulting in a sample size of 71 individuals. The research instrument used is a Likert Scale questionnaire with five answer options. Validity and reliability testing were performed using SPSS version 24. Data analysis involved the Product Moment Correlation test to examine the relationship between the two variables and the significance testing of the correlation using the t-test formula. The data analysis results show that 1) teacher's work motivation is at a relatively high interpretation level, at 79.40%, 2) the school principal's transformational leadership is interpreted as good, at 86.04%, and 3) there is a significant relationship between the two variables with a correlation coefficient of 0.550 and a correlation significance test of 5.465. Based on the research findings, it can be concluded that the school principal's transformational leadership is one of the factors that influence teacher's work motivation. This means that the higher the school principal's transformational leadership, the higher the motivation of teachers in the Lubuk Basung District Public High School.